On the Way to Dominating Cognition - Pogossian, Edward M. (Mathematical Problems of Computer Science, 2021)
Humans become powered enough to question the further types of their being in the universe but have not answers yet whether the solutions are in the corrections of their genomes , discovering of new types of organizations of humans or in transition to a new type of descends, humanoid machines or others. Assuming that scenarios with dominating cognition are the most promising to resolve the challenges of evolvement of humans and are the most expected for the next stage of their being, while the kernel of effective cognition is universal for all types of further being of humans, we present constructive models of the kernel, question the completeness of representations and ways of its further study.